Semi Smooth Graceful Labeling on Some Graphs - V. J. Kaneria; Meera Meghpara (International Journal of Mathematics And its Applications, 2015)
This paper contains some results on semi smooth graceful graph. We proved that $B_{m,n}$, $S^{'}(B_{m,n})$ and $S^{'}(P_{n})$ are semi smooth graceful and a graph obtained by joining $G$ and $B^{2}_{m,n}$ with an arbitrary path $P_{r}$ is a graceful.